Albumin Conjugates of Thiosemicarbazone and Imidazole‐2‐thione Prochelators: Iron Coordination and Antiproliferative Activity. (10th June 2021) - Sung, Yu‐Shien; Wu, Wangbin; Ewbank, Megan A.; Utterback, Rachel D.; Marty, Michael T.; Tomat, Elisa
Abstract: The central role of iron in tumor progression and metastasis motivates the development of iron‐binding approaches in cancer chemotherapy. Disulfide‐based prochelators are reductively activated upon cellular uptake to liberate thiol chelators responsible for iron sequestration. Herein, a trimethyl thiosemicarbazone moiety and the imidazole‐2‐thione heterocycle are incorporated in this prochelator design. Iron binding of the corresponding tridentate chelators leads to the stabilization of a low‐spin ferric center in 2 : 1 ligand‐to‐metal complexes. Native mass spectrometry experiments show that the prochelators form stable disulfide conjugates with bovine serum albumin, thus affording novel bioconjugate prochelator systems. Antiproliferative activities at sub‐micromolar levels are recorded in a panel of breast, ovarian and colorectal cancer cells, along with significantly lower activity in normal fibroblasts. Abstract : Targeting the altered iron metabolism of cancer cells, disulfide‐based prochelators are activated for metal coordination upon intracellular reduction. Novel substituted thiosemicarbazone and imidazole‐2‐thione systems covalently modify bovine serum albumin forming stable bioconjugate prochelators. Antiproliferative activities at sub‐micromolar levels are recorded in breast, ovarian, and colon cancer cell lines.